Depressive symptomatology and its relationship to physical activity in students from sport-oriented universities - Lopez-Salamanca, David Eliecer; Tonguino-Rosero, Stefanie; Agudelo-Orozco, Alexander (Universidad y Salud, 2022)
Introduction: Depression is a public health problem that has a burden of high mortality, mainly affecting the young university student population. The evidence suggests that participation in physical activity generates mental health benefits. It is important to study this association as well as the relationship between depression and sociodemographic variables and university program. Objective: To estimate the prevalence of depressive symptomatology and assess whether physical activity levels can be a Protective factor in university students enrolled in sports programs. Materials and methods: Cross-sectional study with a representative sample of 291 students. The Beck II questionnaire and long version of the International Physical Activity Questionnaire (IPAQ) were applied. Univariate and bivariate analyses were performed with prevalence ratios for depression, according to the level of physical activity adjusted by generalized regression models with logarithmic link of binomial distribution. Results: The prevalence rates of depression symptoms and physical inactivity were 27% and 22%, respectively. The prevalence of depression symptoms is 46% higher in those who are not sufficiently active (RP: 1.46 IC95%:0.95–2.25). Conclusions: Prevalence of depressive symptoms and physical inactivity were lower compared to similar populations and are probably related to the sport focus of the institution.